Interpectoral tuberculous lymphadenitis masquerading as carcinoma breast: A case report - Hariharan, Nisha; Rao, T Subramanyeshwar; Naidu, Chandra C K; Murthy, Sudha M; Vasala, Anjaneyulu; Koppula, Veeraiah; Rayani, Basanthkumar; Dayanand, Krishnakumar (Indian Journal of Case Reports, 2020)
Carcinoma of the breast is showing a rising trend in India and is an important diagnosis in an elderly postmenopausal lady presenting with a breast mass. Clinical assessment and mammography are the initial diagnostic tools. Unfortunately, in India, tuberculosis (TB)continues to remain an important public health problem. While mammary TB is relatively rare and has traditionally been described in young lactating multiparous women, this clinical picture can at times be misleading. TB is known to be a great masquerade, and TB granulomatous mastitis often mimics malignancy in the breast. An accurate diagnosis is essential as the treatment for these two entities is entirely different. We present a case of a breast lump in an elderly postmenopausal lady, which at the time of surgery, proved to be a caseating TB interpectoral node.